Limits on D-0-(D)over-bar(0) mixing and CP violation from the ratio of lifetimes for decay to K-pi(+), K-K+, and pi(-)pi(+) - Aubert, B; Barate, R; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2003)
A measurement of D0-D̄0 mixing parameters was presented using the ratios of lifetimes extracted from samples of D0 mesons decaying to K-π+, K-K+ and π-π+. The size and decay-time characteristics of backgrounds in the data were determined in the likelihood fits without using any Monte Carlo (MC) input. The resulting effect on the fitted lifetime was reported as one source of systematic uncertainty.